Hubungan Antara Karya Desain Grafis dengan Pengembangan Pengetahuan Ekonomi Dasar untuk Anak Usia 3-6 Tahun - Andrian Ekaputra; Paulina Tjandrawibawa (Universitas Ciputra Surabaya, 2018)
This research theme is about how graphic design can help introducing basic economic value to kids. The main purpose is to find out how is the ideal book for kids and parents. The methods which use by author are based on primary and secondary data, which author do interview to expert and extreme user, and use literature data for complementary the primary data.